Metodisk indsamling af transportrelaterede målsætninger og visioner i korridoren Oslo- Göteborg-København-Berlin. - Lundgaard, Jacob (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
This paper describes how an overview of existing aims and visions regarding social devel-opment and transport systems was developed as a part of the Interreg IIIB program funded project COINCO – Corridor of Innovation and Cooperation. The project started up June 2005 and ends in April 2007. The development of this overview lasted from June 2005 to October 2005 and ended up in a database with more than 1000 entries dealing with aims, visions and means from Nor-way, Sweden, Denmark and Germany. By the development of this database it is now possible to search for aims and visions within the project area within a number of categories such as the source of it, country of origin, its subject, whether it is an already decided project or not etc. The result is an example on how to establish a planning foundation for new cross national cooperation.